2017
DOI: 10.4236/aim.2017.71006
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Activity of Colistin and Vancomycin or Azithromycin Combinations on Extensively Drug Resistant <i>Acinetobacter baumannii</i> Clinical Isolates

Abstract: Background: Extensively drug resistant Acinetobacter baumannii (XDR-AB) presents an increasing challenge to health care in Egypt as they are among the most common bacteria isolated in hospital setting. Treatment of such infections usually involves the use of antimicrobial agents in combination. Various combinations have been proposed, with colistin serving as the backbone in many of them even for colistin resistant isolates. Aim: The study was conducted in order to test the in vitro combined effects of colisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Azithromycin enhanced the effect of colistin in AZ/colistin combination, and this was in accordance with previous results reporting the synergistic effect of this combination in resistant isolates of K. pneumoniae and E. coli (60,61) . The obtained values of FICI corresponding to AZ/colistin were in accordance as well with another study investigating the effect of the combination in A. baumannii (62) . Saini et al (63) detected synergy upon combining AZ with ciprofloxacin when tested in P. aeruginosa.…”
Section: Discussionsupporting
confidence: 90%
“…Azithromycin enhanced the effect of colistin in AZ/colistin combination, and this was in accordance with previous results reporting the synergistic effect of this combination in resistant isolates of K. pneumoniae and E. coli (60,61) . The obtained values of FICI corresponding to AZ/colistin were in accordance as well with another study investigating the effect of the combination in A. baumannii (62) . Saini et al (63) detected synergy upon combining AZ with ciprofloxacin when tested in P. aeruginosa.…”
Section: Discussionsupporting
confidence: 90%
“…These findings indicate that vancomycin-containing regimens may provide therapeutic benefit for MDRAB-associated infections; However, other methods should be used to confirm such a synergy. Also optimal combination therapy in severe infections should be considered in a prospective clinical trial (14). In a study, conducted in 2013 they found that combinations of colistin resistant A. baumannii strains isolated from patients previously treated with colistin were synergistic with vancomycin-colistin containing combinations in an in vivo study and in vivo larval experiments have reported that the combination regimen containing colistin-vancomycin-doripenem increases survival compared to monotherapy (15).…”
Section: Discussionmentioning
confidence: 99%